Experimental and numerical studies on the use of a needle for variable capacity single-phase ejectors. (December 2022) - Rand, Charles P.; Croquer, Sergio; Poirier, Michel; Poncet, Sébastien
Highlights: A single-phase supersonic ejector working with R245fa is considered. Advanced numerical modeling is favorably compared to experimental data. A movable needle is used to control the throat area in the primary nozzle. Two needle geometries are tested over a large range of operating conditions. The maximum transiting exergy efficiency is less than 35% in all conditions. Abstract: Vapor ejectors raise interest for cooling applications given their low electrical consumption, however, a single ejector suffers from a lack of capacity flexibility. The current study explores the use of an adjustable needle to control the primary nozzle throat area ( A t ) in view to allow variable ejector capacity. Tests were done using a large scale test bench working with the refrigerant R245fa. CFD simulations using k- ω SST and, for the first time, Scale-Adaptive Simulation (SAS), were also done. A comparison of the simulation results using the two different turbulence models ( ω SST and SAS) showed negligible difference. Also, the simulation results with the ω SST model showed good agreement with the experimental values. For fixed operating conditions, the simulation showed that the reduction of the throat area from 1.00 A t to 0.61 A t increased the entrainment ratio from 24% to 56%, but reduced the critical outlet pressure from 440 kPa to 315 kPa. For all conditions, the transiting exergy efficiency η t r, e x first increased with the increase of the outlet pressure ( P o u t ), reached a maximum value when Pout is close to the critical outlet pressure ( P c r i t ), and then decreased sharply due to the decrease of the entrainment ratio. Finally, CFD modelings with a blunt tip needle to see the effect of the needle geometry and in order to have a lower throat area value of 0.39 A t . This novel study shows that the ejector equipped with a needle is able to maintain ejector performance with changes in operating conditions.